Pengaruh Pendekatan Bermain terhadap Hasil Passing Bola Basket pada Siswa Kelas VIII Di SMP Negeri 3 Palembang - Robby Marsalleno Saputra; Sukardi Sukardi; Ilham Arvan Junaidi (Journal of Creative Student Research, 2025)
The problem in this research is whether there is an influence of playing approach on the results of basketball passing in class VIII students at SMP Negeri 3 Palembang? This research aims to determine whether there is an influence of playing approach on basketball passing results in class VIII students at SMP Negeri 3 Palembang. The research method used is experimental research. The data collection techniques used in this research are observation and tests. Based on the results of research involving 30 students of SMP Negeri 3 Palembang, it was found that the T-count value in the experimental group using the playing approach method was -5.517. A negative T value indicates that the mean score on the pretest is smaller than the posttest score. This means that a negative Tcount value is considered a positive value so that the Tcount in the playing approach experimental group becomes 5.517. Meanwhile, the T table value is 1.699 which is taken from the T table α 0.05 (30-1) = 29. It can be seen above that the results of the t value in the experimental group using the playing approach method are -5.517. Obtained from the experimental group, the Sing.(2-tailed) value was 0.000, which is smaller than α 0.05. This indicates that there is a significant difference between the pretest and posttest results. So a decision can be made that Ha is accepted while Ho is rejected. See table 4.5. This shows that training using the playing approach method has a significant influence on the passing ability in learning basketball in class VIII students at SMP Negeri 3 Palembang.